Prevalence and Patterns of Smoking, Alcohol Use, and Illicit Drug Use in Young Men Who Have Sex with Men - Newcomb, Michael E. (2014)
BACKGROUND: Young men who have sex with men (YMSM) are substantially more likely to use illicit drugs and other substances compared to their heterosexual peers. Substance use during adolescence has critical implications for long-term physical and mental health, and among YMSM may lead to HIV infection. The goal of the current study was to describe lifetime and past six month prevalence and patterns of substance use across multiple substances in a community sample of racially-diverse YMSM. METHODS: Participants were 450 YMSM aged 16–20 living in Chicago and surrounding areas who were recruited beginning December, 2009 using a modified form of respondent driven sampling. Analyses were conducted with multivariate logistic regression and latent class analysis (LCA). RESULTS: Prevalence of substance use was high in this sample of majority racial minority YMSM, and only 17.6% reported no substance use during the past six months. Black YMSM had lower prevalence of use of all substances except marijuana compared to White YMSM, while Latino YMSM had lower prevalence of alcohol, marijuana, and club drug use. Bisexual YMSM reported higher prevalence of cigarette smoking, stimulant use, and club drug use compared to gay/mostly gay YMSM but lower numbers of bisexual participants limited the ability to detect statistically significant differences. LCA found that YMSM fell into three general categories of substance users: alcohol and marijuana users, polysubstance users, and low marijuana users. CONCLUSIONS: Analyses reveal important group differences in prevalence and patterns of substance use in YMSM that have important implications for intervention.